Heranças de fé no sertão do São Francisco: devotos e romeiros na tradicional festa de Santo Antônio em Serra das Araras/MG - Barbosa, Denílson Meireles (2016)
This thesis is aimed at researching the tradition of the pilgrimages of Saint Anthony, inherited for generations and often carried out by family members, which occur in the hinterland of the San Francisco River valley in the north of the state of Minas Gerais. The delimited empirical field is the village of Serra das Araras, the place of the centennial celebration that attracts every year thousands of people. In order to carry out this research, fieldwork was done during and beyond the festival period. Some groups of pilgrims were followed for two years running, from the organization of the material structure to the arrival at the village of Serra das Araras, having been followed along the festival in order to observe, describe and analyze the devotional practices. A field diary was used to facilitate the daily data records within the party. Interviews with pilgrims and devotees were conducted during and outside the festival period, prioritizing the older ones by considering the accumulation of knowledge and practices in the history of this tradition celebrated annually. The was an attempt to address the aspects of inheritance and memory in the traditional festival by using authors who could serve as a reference to understand and interpret, from the concepts proposed by them, the pilgrimages and devotional practices within the festival. Considering the individual and collective experience of the devotees and pilgrims involved annually with this tradition, it is perceived the need to understand the relevance of the form of maintenance of knowledge and religious practices in the cultural context of the festival